Sea lice removal by cleaner fish in salmon aquaculture: a review of the evidence base - Overton, Kathy; Barrett, Luke T.; Oppedal, Frode; Kristiansen, Tore S.; Dempster, Tim (Aquaculture Environment Interactions, 2020)
Stocking cleaner fish to control sea lice infestations in Atlantic salmon farms is widespread and is viewed as a salmon welfare-friendly alternative to current delousing control treatments. The escalating demand for cleaner fish (~60 million stocked worldwide per year), coupled with evidence that they experience poor welfare and high mortality in sea cages, requires that the lice removal effect of cleaner fish be substantiated by robust evidence. Here, we systematically ana lysed (1) studies that tested the delousing efficacy of cleaner fish species in tanks or sea cages and (2) studies of spatial overlap—and therefore likely encounter rate—between cleaner fish and salmon when stocked together in sea cages. Only 11 studies compared lice removal between tanks or cages with and without cleaner fish using a replicated experimental design. Most studies had insufficient replication (1 or 2 replicates) and were conducted in small-scale tanks or cages, which does not reflect the large volume and deep cages in which they are deployed commercially. Reported efficacies varied across species and experimental scale: from a 28% increase to a 100% reduction in lice numbers when cleaner fish were used. Further, our review revealed that the interaction of cleaner fish and salmon in sea cages has rarely been documented. While much of the evidence is promising, there is a mismatch between the current evidence and the extent of use by the industry. We recommend replicated studies in 9 key areas at a full commercial scale across all species that are currently widely used. More targeted, evidence-based use of cleaner fish should increase their efficacy and help to alleviate economic, environmental, and ethical concerns.